The Relationship Between Transformational Leadership Style and Innovative Behavior of Physical Education Teachers and School Principals Mediated by the Quality of Educational Services - Manouchehr Tatari; Sedigh Saeidi (Research in Sport Management and Marketing)
Purpose: The existence of creative and innovative people in education and other scientific and educational centers is more necessary. The main purpose of this study is to investigate the relationship between transformational leadership style and innovative behavior of physical education teachers and school principals through the quality of educational services in girls' schools in Chaharmahal and Bakhtiari province.Methods:This research is applied in terms of purpose and descriptive-correlational. The statistical population of this study is all principals of girls' schools with 505 and all female physical education teachers with 220 students in Chaharmahal Bakhtiari province. The statistical sample of this study was selected using Morgan table and randomly selected 220 school principals and 140 physical education teachers. Data collection tools were Bass and Olivo Transformational Leadership Questionnaire, Standard Questionnaire for Quality of Educational Services and Innovative Behavior Questionnaire for Physical Education Teachers. To determine the validity of the measuring instrument, the validity method of structural analysis was used and the reliability coefficients of the questionnaires based on Cronbach's alpha were 0.93 and 0.75, respectively. In this study, in order to analyze the data, descriptive statistics (mean, standard deviation and variance) and tilt and elongation test were used to check the normality of the data and Pearson correlation tests were used to test the hypotheses. This data processing operation is performed by SPSS software version 23.Results: The results indicate that there is a significant relationship between the transformational leadership style of school principals and the innovative behavior of physical education teachers  (r = 0.214) and the quality of educational services (r = 0.215).There is a significant relationship between the quality of educational services and innovative behavior of physical education teachers (r = 0.418) and there is a significant relationship between transformational leadership style and innovative behavior of physical education teachers and school principals mediated by the quality of educational services.Conclusion: By adopting a transformational leadership style, it is possible to improve the quality of educational services in order to create innovative behaviors in physical education teachers.